2015
DOI: 10.1111/evj.12476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of disinfectant efficacy when using high‐volume directed mist application of accelerated hydrogen peroxide and peroxymonosulfate disinfectants in a large animal hospital

Abstract: For the organisms evaluated, all 3 disinfectants applied as a directed mist were effective at reducing CFUs in a veterinary hospital environment. Effective disinfection using this method of application is dependent on adequate cleaning prior to application, and use of adequate volumes of disinfectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…A recent paper examining disinfection efficacy against several common bacterial pathogens in a large animal hospital environment showed an approximately 90% reduction in colony-forming units per milliliter of S enterica when either an accelerated hydrogen peroxide or peroxy monosulfate disinfectant product was used via a mist application technique, provided adequate cleaning was performed first. 46 As with antimicrobial drugs, disinfectants have a spectrum of activity that can be highly variable between disinfectant classes. 1 Examples of disinfectants commonly used in veterinary medicine include bleach (sodium hypochlorite), quaternary ammonium, phenols, and peroxides.…”
Section: Prevention and Control Adult Cowsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper examining disinfection efficacy against several common bacterial pathogens in a large animal hospital environment showed an approximately 90% reduction in colony-forming units per milliliter of S enterica when either an accelerated hydrogen peroxide or peroxy monosulfate disinfectant product was used via a mist application technique, provided adequate cleaning was performed first. 46 As with antimicrobial drugs, disinfectants have a spectrum of activity that can be highly variable between disinfectant classes. 1 Examples of disinfectants commonly used in veterinary medicine include bleach (sodium hypochlorite), quaternary ammonium, phenols, and peroxides.…”
Section: Prevention and Control Adult Cowsmentioning
confidence: 99%
“…The principle advantage of phenols is better activity in organic debris. Peroxides are increasingly used for environmental disinfection, footbaths, and environmental misting and fogging, 1,46 and are perceived as being more environmentally friendly than chemicals such as phenols and bleach. Chlorine dioxide is a powerful oxidant as well as disinfectant, and it can be used to remove and prevent biofilm formation.…”
Section: Prevention and Control Adult Cowsmentioning
confidence: 99%
“…Thus, the disinfection of the livestock and poultry houses has become an important measure to prevent and control diseases. The commonly used chemical disinfectants for broiler houses include available chlorine, ozone, quaternary ammonium salt, and glutaraldehyde ( Meroz and Samberg, 1995 ; Saklou et al, 2016 ; Chidambaranathan and Balasubramanium, 2017 ). The different disinfectants used for large-scale disinfection of broiler houses operate via different mechanisms, and thus, their disinfection efficacies also differ ( Suwa et al, 2013 ; Chidambaranathan and Balasubramanium, 2017 ; Maertens et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosolized disinfectants have been applied for more than half a century. Aerosol can conserve materials and form a disinfecting aerosol-disinfectant vapor gas system ( Wichelhaus et al, 2006 ; Carvalho et al, 2015 ; Saklou et al, 2016 ). With the application of ultrasonic atomization technology, liquids can be atomized into an aerosol state to obtain uniformly dispersed 2–4 μm droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new peroxygen disinfectant, 4.25% hydrogen peroxide, has become available that the manufacturer reports to have broad antimicrobial activity (labeled as a broad‐spectrum fungicide, virucide, and bacteriocide), and anecdotally is reportedly to be less corrosive on surfaces. We have shown that this product is comparable to other commonly used disinfectants in a directed mist application . However, there currently are no published reports evaluating this product in a footmat application.…”
mentioning
confidence: 76%